THU0476 Serum Osteoprotegerin Ve Trail Levels in Patients with Behcet's Disease. (23rd January 2014) - Karaveli, G.; Olmez, U.; Kucuksahin, O.; Ozguclu, S.; Tutkak, H.; Ates, A.; Duzgun, N.
Abstract : Background: Behçet's disease (BD) is an inflammatory disease with unknown etiology characterized by recurrent, oral and genital ulcers, uveitis and skin lesions. Osteoprotegerin (OPG), a glicoprotein which is a member of tumor necrotising factor (TNF) family functions in the regulation of bone resorption. Recent studies indicate that OPG and TRAIL has an important role in the development of vascular and inflammatory disease. But there was no research that compares OPG and TRAIL serum levels between patients with Behçet disease (BD) who have recurrent aphthous ulcer (RAU) and healthy control group. Objectives: The aim of the present study was to investigate OPG and TRAIL levels in serum samples of BD patients, patients with recurrent aphtous ulcers ad healthy controls and to compare serum OPG and TRAIL levels between study groups. Methods: 65 patients fulfilling the International Study Group criteria with the diagnosis of BD, 31 patients with recurrent aphtous ulcers (RAU) and 30 healthy controls indiciduals were included in the study. ELISA (enzyme-linked immunosorbent assay) method was used for the measurement of serum OPG and TRAIL levels by using Raybiotech Human OPG and Bioscience Human TRAIL Platinum ELİSA kits. Results: Sixty-five BD patients (37 male and 28 female) with mean age of 41, 8±10, 4 years and 31 patients with RAU (13 male and 18 female, mean age of 37, 8±13, 5 years). Serum OPG levels were found to be 1, 42±1, 43 pg/ml in BD group 2, 05±1, 92 pg/ml in RAU group and 1, 19±0, 47 pg/ml in healthy controls. No significant difference was seen between study groups in terms of OPG levels (p> 0, 05). When compared RAU patients to BD patients, OPG levels were found to be significantly lower in BD group (p=0, 017). Serum TRAIL levels were found to be 13, 1±7, 94 pg/ml in BD group, 15, 31±5, 41 pg/ml in RAU group and 18, 02±12, 63 pg/ml in healthy control group. Serum TRAIL levels were significantly lower in BD group than healthy control group (p=0, 037 and p=0, 024, respectively). Conclusions: Even though there is research in literature that supports the role of OPG and TRAIL in the development of vascular and inflammatory diseases, this research shows that OPG and TRAIL has no significant impact in the development of vascular and inflammatory diseases, because of the low levels of OPS and TRAIL observed in patients with BD and the insignificant correlation between ESR and CRP levels. However, due to insufficient scoring of active patients in this study, research including patients with recent diagnoses and active vascular disease is required to confirm the findings in this study. References: Yazıcı H, Yurdakul S, Hamuryudan V.Behcet's Syndrome. Curr Opin Rheumatology 1999;11:53-57 Yun TJ, Tallquist MD, Aicher A, Rafferty KL, Marshall AJ, Moon JJ, Ewings ME, Mohaupt M, Herring SW, Clark EA. Osteoprotegerin, acrucial regulator of bone metabolism, also regulates B cell development and function. J Immunol 2001; 166: 1482–1491. Disclosure of Interest: None Declared